Dynamic testing with graduated prompts training: Adolescents with executive function deficits. - Fogel, Yael (Hong Kong Journal of Occupational Therapy, 2025)
Introduction: Adolescents with executive function deficits have difficulties performing complex daily tasks. Process-oriented dynamic testing with graded prompts training offers valuable insights to improve adolescents' thinking and performance abilities in occupational therapy interventions. This study explores the effectiveness of graded prompts training in improving performance during the Rey-Osterrieth Complex Figure (ROCF) task. Method: This secondary analysis included data from 41 adolescents with executive function deficit profiles who had participated in the therapeutic occupational therapy intervention program 'Functional Individualized Therapy for Teenagers'. Dynamic pre- and post-test phases, focused on copying and immediate recall, were assessed using accuracy, placement, and organization strategy scores. Results: Results indicate significant improvements following graded prompts training in copying and memory accuracy (67% and 180%), placement (49% and 237%), and organization strategy (66% and 99%). Positive correlations were observed between improved copying accuracy and organization, memory accuracy and organization, and copying and memory organization (p <.001). Conclusion: Graded prompts training may improve the performance of adolescents with executive function deficits during complex tasks (e.g., ROCF). Future research should explore the training's long-term effects and applications in diverse clinical settings to validate further and expand these promising results. This training could become integral to therapeutic interventions for enhancing this population's daily functioning and overall well-being.